The Comic in Folk-lore - Donatas Sauka (Literatūra (Vilnius))
The present article is a study of the comic in folk-lore ranging from jokes and nicknames (as a lower level) to humorous folk-tales and songs (as more developed forms). Lithuanian folk poetry is of particularly high artistic excellence. Vivacity, laconism, witty alliteration, on one hand, and their ethical contents, on the other, place humorous songs on a par with the best laments and songs of sorrow.